Advanced Biological Treatment Processes - Wang, Lawrence K.; Shammas, Nazih K.; Hung, Yung-Tse. (Handbook of Environmental Engineering ;, 2009)
Volume 9: Advanced Biological Treatment Processes in the Handbook of Environmental Engineering series provides critical insight into pollution-abatement engineering. This outstanding collection of methodologies is designed as a review of engineering systems currently being used, as well as their potential for use in pollution abatement. The books expert panel of authors provides a look at a range of topics, including principles and kinetics of biological processes, vertical shaft bioreactors, upflow sludge blanket filtration, membrane bioreactors, column bioreactor, SBR, nitrification, denitrification, and emerging biological processes. Volume 9: Advanced Biological Treatment Processes and its sister book - Volume 8: Biological Treatment Processes are indispensable as both basic biological treatment textbooks and comprehensive reference books for advanced undergraduate and graduate students, designers of waste treatment systems, scientists, and researchers. A gold-standard addition to The Humana Press series, Volume 9: Advanced Biological Treatment Processes gives readers a cutting-edge illustration of the theory and practice of biological abatement systems and their critical role in environmental issues today.